Genetic Diversity Assessment Among Early Generation Sugarcane (Sacccharum Officinarum L.) Clones Through Microsatellite Markers (Applied Biological Research, 2017)
The present study was aimed to characterize the early generation  sugarcane (Saccharum officinarum) clones. Thirty-four sugarcane  genotypes from different cross combinations representing six bi parental crosses, twenty-four general crosses, three poly-crosses and  one-selfed were planted along with two checks. A total of 20 SSR  markers were used to assess the gen etic diversity of which 93.5%  were polymorphic. Polymorphic information content was used to  determine allele diversity at each locus ranged from 0.141  (SOMS118) to 0.314 (UGSM585). The average expected gene  diversity ranged from 0.105 (SOMS120) to 0.396 (UGSM-585).  Genetic similarity based by Jaccard’s similarity coefficient ranged  from 0.419 to 0.96. Dendrogram constructed using UPGMA cluster  analysis revealed two distinct groups among S. officinarum species  clones and two commercial checks and ordered the populations of 36  genotypes into five clusters with varying number of members proved SSR  marker to be an effective tool for assessing genetic diversity among  sugarcane clones.
Keywords: Genetic diversity; simple sequence repeat; polymorphism; saccharum; sugarcane